Sickle red blood cell‐derived extracellular vesicles activate endothelial cells and enhance sickle red cell adhesion mediated by von Willebrand factor. (5th January 2023) - An, Ran; Man, Yuncheng; Cheng, Kevin; Zhang, Tianyi; Chen, Chunsheng; Wang, Fang; Abdulla, Fuad; Kucukal, Erdem; Wulftange, William J.; Goreke, Utku; Bode, Allison; Nayak, Lalitha V.; et al.
Summary: Endothelial activation and sickle red blood cell (RBC) adhesion are central to the pathogenesis of sickle cell disease (SCD). Quantitatively, RBC‐derived extracellular vesicles (REVs) are more abundant from SS RBCs compared with healthy RBCs (AA RBCs). Sickle RBC‐derived REVs (SS REVs) are known to promote endothelial cell (EC) activation through cell signalling and transcriptional regulation at longer terms. However, the SS REV‐mediated short‐term non‐transcriptional response of EC is unclear. Here, we examined the impact of SS REVs on acute microvascular EC activation and RBC adhesion at 2 h. Compared with AA REVs, SS REVs promoted human pulmonary microvascular ECs (HPMEC) activation indicated by increased von Willebrand factor (VWF) expression. Under microfluidic conditions, we found abnormal SS RBC adhesion to HPMECs exposed to SS REVs. This enhanced SS RBC adhesion was reduced by haeme binding protein haemopexin or VWF cleaving protease ADAMTS13 to a level similar to HPMECs treated with AA REVs. Consistent with these observations, haemin‐ or SS REV‐induced microvascular stasis in SS mice with implanted dorsal skin‐fold chambers that was inhibited by ADAMTS13. The adhesion induced by SS REVs was variable and was higher with SS RBCs from patients with increased markers of haemolysis (lactate dehydrogenase and reticulocyte count) or a concomitant clinical diagnosis of deep vein thrombosis. Our results emphasise the critical contribution made by REVs to the pathophysiology of SCD by triggering acute microvascular EC activation and abnormal RBC adhesion. These findings may help to better understand acute pathophysiological mechanism of SCD and thereby the development of new treatment strategies using VWF as a potential target.